The Influence of Multiple Intelligences on Individual Capacity in Building Counter-Radicalism Narratives - Achmad Azis Abidin; Raharjo; Mundhir (Universitas Nahdlatul Ulama Surabaya, 2025)
Proclaiming inclusive Islam requires a good narrative so that the values of Islamic inclusiveness can be conveyed on target. This article investigates the influence of multiple intelligence on an individual's capacity to build a counter-radical narrative. Using the theoretical framework of Howard Gardner's Multiple Intelligence, this research considers how multiple intelligence such as verbal-linguistic intelligence, logistic-mathematical intelligence, visual-spatial intelligence, and musical intelligence, kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, naturalist intelligence, and existential intelligence influence an individual's ability to design narratives that are contrary to radical ideology. The research methods used include surveys and analysis of respondents with a variety of multiple intelligences to reveal the role and impact of these intelligences on their ability to build a counter-radicalism narrative. The results of this research show that there is a significant influence of multiple intelligences on individual capacity in building counter-radicalism narratives, as well as the importance of developing multiple intelligences in approaches to preventing radicalism.